Optimalisasi Pengelolaan Zakat dalam Program Palembang Pintar pada Baznas Kota Palembang - Annur, Saipul; Izzaya, Haikal; Ibrahim, Ibrahim (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the optimization of zakat management in the "Palembang Pintar" program at the National Amil Zakat Agency (Baznas) of Palembang. This research employs a qualitative approach with a descriptive method. The study involves 15 informants, including the head of Baznas, deputy head, treasurer, staff, and beneficiaries of the "Palembang Pintar" program. Data collection methods include interviews, observations, and documentation. Data analysis techniques involve data collection, presentation, verification, and conclusion drawing, with data validity ensured through triangulation. The results and discussion indicate that the optimization of zakat management in the "Palembang Pintar" program at Baznas Palembang has been effectively implemented. This process includes several stages: determining the program's budget, socialization, selection of program beneficiaries (mustahiq), supervision of experts and mustahiq, and final reporting on the program's success or failure.